(untitled) (Bangladesh Journal of Otorhinolaryngology, 2009)
A 40 year old man was admitted to Shaheed Suhrawardy hospital, Dhaka with swelling of left parotid gland and left eye ball. Previously incisional biopsy was done from upper conjuntival swelling at National Institute of Opthalmology (NIO), Dhaka which revealed moderately differentiated Squamous cell carcainoma. Later on FNAC of left parotid swelling was done which revealed poorly differentiated adenocarcinoma. The patient under went left Radical Parotidectomy with left sided selective neck dissection and exenteration of left eye ball at SSH, Dhaka. Histopathology report showed poorly differentiated carcinoma of parotid, conjunctival tissues & necknodes. As synchronous malignancy of parotid gland, eyeball with metastatic neck nodes is rare, so this case has been selected to publish in the medical journal. Key words: Parotid, Eye ball, Synchronous Malignancy. Bangladesh J of Otorhinolaryngology 2008; 14(2) : 75-77